ANALISA STRATEGI KOMUNIKASI PEMASARAN ONLINE DAN OFFLINE PADA INDUSTRI PERHOTELAN DI BALI TERHADAP KEPUTUSAN PEMBELIAN WISATAWAN EROPA - astuti, ayu (Universitas Pendidikan Nasional, 2018)
ABSTRACTBali is a renowned travel destination that is visited by travelers from all over the world. European travelers, particularly, has been one of the largest share markets that visit and spend their holiday in Bali since a long time ago. Marketing communication campaigns are executed by practitioners in hospitality industry to grab European market share, through not only traditional media, but also digital or online media, to increase room nights as well as revenue. This study focuses to identify the effectiveness of online and offline Integrated Marketing Communication strategy towards the buying decision of European travelers, including their behavior in the process of decision-making. Do the marketing communication strategies through traditional media influence them in choosing a hotel, or does the tendency of using new technology make the online media play more roles in decision-making? Knowing which media is effective, it is beneficial to the companies in hospitality industry in Bali to understand the behavior of the clients’ decision-making and to push their marketing communication campaigns through the right medium that influences their clients’ buying decision.Keywords :Integrated Marketing Communication, , European Tourist Consumer Behavior, Travel Agent , Online Travel Agent .Purchase Decision